2012
DOI: 10.1371/journal.pone.0050077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin Therapy on Myocardial Lipid Content and Cardiac Geometry in Patients with Type-2 Diabetes Mellitus

Abstract: Aims/HypothesisRecent evidence suggests a link between myocardial steatosis and diabetic cardiomyopathy. Insulin, as a lipogenic and growth-promoting hormone, might stimulate intramyocardial lipid (MYCL) deposition and hypertrophy. Therefore, the aim of the present study was to investigate the short-term effects of insulin therapy (IT) on myocardial lipid content and morphology in patients with T2DM.MethodsEighteen patients with T2DM were recruited (age 56±2 years; HbA1c: 10.5±0.4%). In 10 patients with insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The reduction in the liver fat fraction with insulin therapy is consistent with the findings of previous studies that have used MRS (6)(7)(8) or computed tomography (9) for quantification and monitoring of fractional liver fat. In parallel to liver fat fraction reduction, our study revealed an average concomitant liver volume decrease of 152 mL in the insulin-treated group.…”
Section: Effect Of Insulin Glargine and Liraglutide On Mr-based Biomasupporting
confidence: 90%
See 1 more Smart Citation
“…The reduction in the liver fat fraction with insulin therapy is consistent with the findings of previous studies that have used MRS (6)(7)(8) or computed tomography (9) for quantification and monitoring of fractional liver fat. In parallel to liver fat fraction reduction, our study revealed an average concomitant liver volume decrease of 152 mL in the insulin-treated group.…”
Section: Effect Of Insulin Glargine and Liraglutide On Mr-based Biomasupporting
confidence: 90%
“…Yet, prior studies that have used imaging techniques for fat quantification have shown a reduction in liver fat with insulin therapy (6)(7)(8)(9). The mechanisms by which insulin therapy may reduce liver fat include inhibition of lipolysis, which may reduce free fatty acid flux to the liver (7), and decreased production of endogenous insulin passing through the liver to stimulate hepatic lipogenesis (6).…”
mentioning
confidence: 99%
“…1). In support of this concept, treatment of patients with T2D with 10 days of exogenous insulin increased the myocardial lipid content by 80%, the level of which was positively associated with the initial mean glucose concentration (18). Even in normal subjects, short-term hyperinsulinemia and hyperglycemia caused an increase in myocardial lipid content, indicative of how hyperinsulinemia together with hyperglycemia can contribute to cardiac lipid accumulation (19).…”
Section: Ir: Offense or Defensementioning
confidence: 92%
“…Our recent studies suggest that MYCL accumulation is not directly related to insulin resistance [ 6 ] and is highly dynamic, quickly responding to changes in the metabolic and hormonal milieu [ 12 14 ]. Furthermore, sufficient MYCL stores might be prerequisite to stimulated systolic function in response to catecholamine-induced stress [ 14 ].…”
Section: Introductionmentioning
confidence: 99%